Temperature Fluctuations Affected the Activity of Triosephosphate Isomerase by Regulating Phosphorylation and Nitrosylation - WU Saisai, WANG Zhenyu, BAI Yuqiang, HOU Chengli, RAO Weili, LI Xin, ZHANG Zhisheng, ZHANG Dequan (Shipin Kexue)
In this study, triosephosphate isomerase was incubated in the presence of exogenous protein kinase A and S-nitrosoglutathione to elucidate the regulatory effects of phosphorylation and nitrosylation on the enzyme’s activity as a function of incubation time. High expression models of triosephosphate isomerase modification by phosphorylation and nitrosylation were constructed under different temperature conditions. The results showed that after 6 h incubation at 4 ℃, the triosephosphate isomerase activity, phosphorylation and nitrosylation levels of the control group were significantly lower than those of the constant temperature + modification group, suggesting that phosphorylation and nitrosylation worked together to improve the activity of triosephosphate isomerase. Compared with the constant temperature + modification group, the effect of phosphorylation on the activity of triosephosphate isomerase was weaker in the amplitude fluctuation + modification group, but stronger in the frequency fluctuation + modification group. After 6 h incubation, the relative content of β-sheet was significantly higher and that of random coil was significantly lower in both fluctuating temperature + modification groups than in the constant temperature + modification group. Atomic force microscopic (AFM) observation found that for all three treatment groups, the dimension of triosephosphate isomerase was smaller at 12 h than at 0 h, but no difference was observed among the three treatment groups. In conclusion, the increase in phosphorylation and nitrosylation levels slowed down the decline in the activity of triosephosphate isomerase in vitro at 4 ℃, and amplitude or frequency fluctuations of incubation temperature affected the regulatory effect of phosphorylation and nitrosylation on triosephosphate isomerase activity, leading to increased activity in the early stages of incubation and inhibiting the structural transition from order to disorder.